Delineation of The Heritage City of Sumbawa Besar - Tri Satriawansyah; Arbi Batulante (Green Publisher Indonesia, 2022)
Pusaka is a relic from the past that has historical value, contains the quality of thought, and has a very important role in the social dimension of human life. Therefore, heritage has a strong influence on the architectural style that is unique to a city. Heritage City can be interpreted as a city in which there are cultural heritage areas and/or cultural heritage buildings that have important values ​​for the city. So that the city places the implementation of heritage planning and preservation activities as the main strategy for developing the city. The parameters used in preparing the heritage city delineation consist of three, namely heritage assets or buildings, social-economy and patterns of relationships/interactions. Based on the results of the classification of heritage city areas, a Heritage City Delineation Map can be compiled. The heritage city delineation is divided into three zones, namely the Core Zone with an area of ​​11.13 ha, the Supporting Zone with an area of ​​29.97 ha, and the Buffer Zone with an area of ​​16.54 ha. The heritage assets included in the Core Zone are the Dalam Loka Palace, the Sultanate Mosque, Bala Puti, Kokar Dano, the Information Office, and the Mina Mano Restaurant. The heritage assets that are included in the Support Zone are Bala Kuning Palace, Bala Datu Ranga, Ex Public Works Office, Bala Batu Ode, Animal Health Office, Doctor's House, Bala Datu Arong, PO Bus Together, Paksing, Japanese Tangsi, and High Builder (New Bud Shop). While the heritage assets inside the Buffer Zone are the Horse Race Field (Prags Field) and Ai Awak.